Perinatalna opieka paliatywna w Polsce. Charakterystyka ilościowa wybranych aspektów - Jarzębińska, Aneta (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2022)
The purpose of this study was a quantitative analysis of data regarding providers, beneficiaries and services related to perinatal palliative care (PPC) in Poland. Results of said study are discussed in this article. The basis for the study was an analysis of data available from websites of perinatal hospices, official data from Poland’s National Health Fund (Narodowy Fundusz Zdrowia, NFZ) regarding PPC service agreements, and an online database containing reports from public organizations. It has been determined that there are 23 institutions offering PPC services in 14 voivodeships in Poland. Between years 2018–2020, these institutions differed significantly in terms of the number of beneficiaries. Furthermore, they were differentiated because of the range of services they offered on their websites. There were also differences related to their financing structures – not all the institutions under analysis have secured an appropriate agreement with NFZ. The obtained results lead to the conclusion that the quality of care for families of a child with a prenatal diagnosis of a lethal defect can depend on the institution which provides help.